Biomechanical analysis of the herringbone technique as employed by elite cross‐country skiers. Issue 3 (4th December 2012) - Andersson, E.; Stöggl, T.; Pellegrini, B.; Sandbakk, Ø.; Ettema, G.; Holmberg, H.‐C.
<x xml:space="preserve">Abstract</x> This investigation was designed to analyse the kinematics and kinetics of cross‐country skiing at different velocities with the herringbone technique on a steep incline. Eleven elite male cross‐country skiers performed this technique at maximal, high, and moderate velocities on a snow‐covered 15° incline. They positioned their skis laterally (25 to 30°) with a slight inside tilt and planted their poles laterally (8 to 12°) with most leg thrust force exerted on the inside forefoot. Although 77% of the total propulsive force was generated by the legs, the ratio between propulsive and total force was approximately fourfold higher for the poles. The cycle rate increased with velocity (1.20 to 1.60 Hz), whereas the cycle length increased from moderate up to high velocity, but then remained the same at maximal velocity (2.0 to 2.3 m). In conclusion, with the herringbone technique, the skis were angled laterally without gliding, with the forces distributed mainly on the inside forefoot to enable grip for propulsion. The skiers utilized high cycle rates with major propulsion by the legs, highlighting the importance of high peak and rapid generation of leg forces.